CSIG-04. BMP4 INDUCTION OF A SENESCENCE-LIKE PHENOTYPE IN HUMAN GLIOBLASTOMA CELLS IS PARTIALLY DEPENDENT ON P21. (14th November 2022) - Niklasson, Mia; Dalmo, Erika; Westermark, Bengt
Abstract: Bone morphogenetic protein 4 (BMP4) was initially suggested as a potential differentiation-inducing factor to be used in the therapy of glioblastoma. We and others have however demonstrated that the response is reversible, variable among patient samples, and heterogeneous within the same cell line. To deepen our knowledge on how BMP4 affects different types of glioblastoma cells, we treated phenotypically different clones from the same patient tumor—a multitherapy-sensitive/proneural-like (SENS/PN) clone and a multitherapy-resistant/mesenchymal-like (RES/MES) clone—with BMP4. In the SENS/PN clone, BMP4 turned on a mesenchymal-related gene program, whereas this response was less prominent in the RES/MES clone. Untreated SENS/PN cells were smaller than RES/MES cells, but both clones responded to BMP4 by cell size enlargement. Increase in cell size has been suggested to precede senescence; young cells are smaller than old cells that eventually enter replicative senescence. BMP4 induced a senescence-like phenotype in a subpopulation of cells, demonstrated by induction of senescence-associated (SA)-β-gal, p21 up-regulation, lamin B1 down-regulation, as well as increased lysosomal mass and granularity. This was more pronounced in the RES/MES clone than in the SENS/PN clone, and it was dependent on canonical SMAD signaling. Senolytic treatment ablated the SA-β-gal positive cells and reduced the p21 level at the population level. Targeted deletion of p21 abolished BMP4-induced SA-β-gal and increase in cell growth, while lamin B1 down-regulation remained, demonstrating that p21 signaling is crucial for one part of the senescence induction by BMP4. We are currently further investigating a connection between cell size, mesenchymality and senescence. We hypothesize that large mesenchymal-like cells are closer to senescence than smaller proneural cells within the cell culture. A combination of senescence-induction and senolytic treatment may open treatment opportunities to target therapy-resistant glioblastoma cells.